Production of [13N]ammonia from [13C]methanol on a 7.5 MeV cyclotron using 13C(p, n)13N reaction: Detection of myocardial infarction in a mouse model. (August 2019) - Nkepang, Gregory N.; Gali, Hariprasad; Houson, Hailey; Hedrick, Andria F.; Hayes, Bryan; Causey, Oliver; Inman, Paul; Box, Jon; Benton, Eric; Galbraith, Wendy; Awasthi, Vibhudutta
Abstract: [ 13 N]Ammonia is commonly produced using 16 O(p, α) 13 N reaction but one of the limiting factor of this reaction is the relatively small nuclear cross-section at proton energies of <10 MeV. An alternative production method using 13 C(p, n) 13 N reaction, which has a higher nuclear cross-section at low proton energies, is more suitable for a preclinical PET imaging facility equipped with a <10 MeV cyclotron. Here, we report a novel method to produce [ 13 N]ammonia from [ 13 C]methanol for preclinical use on a 7.5 MeV cyclotron. A tantalum solution target (80 μl) consisting of a havar window supplied by the cyclotron manufacturer for the production of [ 18 F]fluoride was used without any modifications. The final bombardment parameters were optimized as follow: [ 13 C]methanol concentration in target solution – 10%, bombardment time – 8 min, and beam current – 2.2 μA. These parameters provided doses of [ 13 N]ammonia which were sufficient to conduct preclinical PET imaging studies in a mouse model of myocardial infarction. Under optimized conditions, the operational lifetime of the target was approximately 150 μAmin. Radionuclide identity of the product as 13 N was confirmed by measuring the decay half-life and its radionuclide purity was confirmed by γ-ray spectroscopic analysis. Gas chromatography revealed that the final [ 13 N]ammonia dose was not distinguishable from water, showing no traces of methanol. As expected, PET/CT imaging in healthy CD-1 mice indicated the accumulation of [ 13 N]ammonia in myocardial tissue; mice with myocardial infarction created by left ascending coronary ligation showed clear perfusion deficit in affected tissue. This work demonstrates the proof-of-concept of using 13 C(p, n) 13 N reaction to produce [ 13 N]ammonia from [ 13 C]methanol with a <10 MeV cyclotron, and its diagnostic application in imaging cardiac perfusion. Highlights: A novel method for production of 13 N-ammonia using low energy cyclotron and 13 C-methanol as target has been described. This method produces radiochemially pure 13 N-ammonia for preclinical use. Injection of 13 N-ammonia, thus produced, demonstrated perfusion deficit in a mouse model of myocardial infarction.